Pasar Tradisional Dengan Pendekatan Form Follows Function Di Rengat - Nivita Tri Mulyeni; Mira Dharma Susilawati; Wahyu Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Traditional Market Design is intended to meet daily needs of the society. Traditional Market in Rengat is not enough to accommodate shopping area, especially in the district of West Rengat, Pematang Rebah located near the capital city. Based on records of Market Department of Indragiri Hulu until 2016, West Rengat sub-district does not have any Traditional Market yet. Traditional Market in Rengat also has discomfort such as dirty environment and management of internal space and outer space that is not regular. This condition becomes the background of this design. Traditional Market Design by using Form Follows Function approach. Research methods used trought field surveys, literature reviews, and building analysis. Approaches are applied partially or completely to the market building. Form Follows Function prioritizes planned spaces according to their function that isintended to meet human needs. The concepts used in this design are Trade Values in Modern Concepts. The application of this concept is contained in the Traditional Market design which includes layout of buildings that have functionality of the site, the spatial placement inthe building in accordance with needs and functions, arrangement of circulation inside and outside the building that facilitate activity of buying and selling, a convenient utility for users, and building facades that are result of the concept.Keywords: Traditional Market, Form Follows Function, Trade Values in Modern Concepts Rengat.